2015
DOI: 10.3109/01612840.2014.981770
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Health Promotion and Consumers with Mental Illness in Australia

Abstract: People with serious mental illness (SMI) have increased risk of cardiovascular disease and premature death, yet research on nurse-provided health promotion in mental health services remains under-developed. This paper informs efforts to improve the nursing role in physical health of consumers with SMI by establishing what nurse perceptions and background influence their care. Members of the Australian College of Mental Health Nursing were invited to participate in an online survey on their views on physical he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Perceived barriers to consumer lifestyle change did not predict health promotion. The effects of nurse–patient collaboration were significant, but small.Happell et al [36] [2012]AustraliaCross-sectional survey. Cardio-metabolic Health Nurse Role133 open comments about the role of the CHN N = 643 see 5.Routine practiceNationalNurses see the specialist role as suitable and valuable for mental health services.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived barriers to consumer lifestyle change did not predict health promotion. The effects of nurse–patient collaboration were significant, but small.Happell et al [36] [2012]AustraliaCross-sectional survey. Cardio-metabolic Health Nurse Role133 open comments about the role of the CHN N = 643 see 5.Routine practiceNationalNurses see the specialist role as suitable and valuable for mental health services.…”
Section: Resultsmentioning
confidence: 99%
“…More knowledgeable/self-efficacious nurses referred patients to smoking cessation resources ( d = 0.41 to 0.8) or provided intensive interventions ( d = 0.45 to 0.73); those with cessation- consistent beliefs more likely to refer ( d = 0.48 to 0.49) or provide intervention ( d = 0.49–0.90) c Verhaege et al [61] [not reported]BelgiumQualitative. Health promotion.Focus groups (staff) interviews (patients) N = 17 MHNs; N = 15 patients homeless serviceRoutine practiceServiceBenefits of physical and mental health identified, but barriers to integrating healthy lifestyles into patients’ lives: lack of time and personal views and attitudes towards health promotion were important. MHNs and care for specific physical health issues: Longitudinal/intervention studies Happell et al [36] [not reported]AustraliaLongitudinal AB survey. Cardio-metabolic health.14-item questionnaire N = 42 nurses initially and N = 21 at follow-up.Introduction of a CHNServiceNurses initially supportive of the role.…”
Section: Resultsmentioning
confidence: 99%
“…However, at the clinical level providing physical health care remains a challenge for many nurses working in mental health setting (Ward, Wynaden, & Heslop, ; Wynaden et al., ). Several studies (Bressington et al., ; Ganiah, Al‐Hussami, & Alhadidi, ; Happell, Platania‐Phung, & Scott, ; Robson, Haddad, Gray, & Gournay, ) have been completed to gain an improved understanding of the challenges nurses experience using a quantitative measurement tool developed by Robson and Haddad (), and to evaluate attitudes nurses hold towards physical health promotion activities (Happell & Platania‐Phung, ; Wynaden et al., ). A qualitative study also identified the need for mental health nurses to change their nursing practices to address the unmet physical health care needs of mental health service users (Gray & Brown, ).…”
Section: Introductionmentioning
confidence: 99%